The Influence of Personality, Ability and Work Motivation on the Work Achievement of Disaster Management Agency Employees Labuhanbatu Regency Area - Hermansyah Hermansyah; Yuniman Zebua; Pitriyani Pitriyani (Budapest International Research and Critics University, 2022)
This study aims to analyze the influence of personality, ability and work motivation on employee performance at the Regional Disaster Management Agency of Labuhanbatu Regency. The population in this study were 90 people. The sampling technique used was saturated sampling, so the sample size in this study was 90 people. The data collection method used a questionnaire/questionnaire. The results of multiple linear regression analysis obtained the equation Y= 1,989 +0,211X1+0,564X2+0,160X3. In the partial test (t test) the personality variable obtained a tcount value of 3.030>ttable1.987 which means that the personality variable has a positive and significant effect on the employee's work performance variable with a significant value of 0.003 <0.05. The ability variable obtained a tcount value of 4.042> t table 1,987 which means that the ability variable has a positive and significant effect on the employee performance variable with a significant value of 0.000 < 0.05. The work motivation variable obtained a tcount value of 2.302> t table 1.987 which means that the work motivation variable has a positive and significant effect on the employee achievement variable with a significant value of 0.024 < 0.05. The results of the F test obtained an F value of 65.211 > Ftable 2.71 with significant value 0.000 <0.05 which means that personality, ability and work motivation simultaneously have a positive and significant effect on employee performance. The results of the coefficient of determination test show that 05 which means that personality, ability and work motivation simultaneously have a positive and significant effect on employee performance. The results of the coefficient of determination test show that 05 which means that personality, ability and work motivation simultaneously have a positive and significant effect on employee performance. The results of the coefficient of determination test show thatpersonality, ability and work motivation variables have an effect of69.5%on the employee's work performance variable, while the remaining 30.5% is influenced by other variables that are outside this research.